Answer:
42°
Step-by-step explanation:
AD bisects ∠CAB, which means it splits ∠CAB into two equal parts. ∠CAB equals 84°. 84° ÷ 2 = 42°.
The 40 oz and $8.00 i think
The measures of the angles are 59 degrees
<h3>How to determine the value of the angles?</h3>
The angles are given as:
Angle 1 = 2x + 17
Angle 2 = 3x - 4
By the interior angle theorem, the angles are congruent
So, we have
Angle 1 = Angle 2
Substitute the known values in the above equation
2x + 17= 3x - 4
Collect the like terms
3x - 2x = 17 + 4
Evaluate the like terms
x = 21
Substitute x = 21 in Angle 1 = 2x + 17
Angle 1 = 2 * 21 + 17
Evaluate
Angle 1 = 59
This means that
Angle 1 = Angle 2 = 59
Hence, the measures of the angles are 59 degrees
Read more about angles at:
brainly.com/question/25716982
#SPJ1
Answer:
66 ≤ f ≤100
Explanation
Mean= ( Σ x ) / n
Mean= sum of scores/ number of subject she took
Now, she already too 3 subject which sum is 85+83+86=254
Now we need to know range of score for her to have (grade) a mark between 80 and 89
Now let take the lower limit mean=80
The lowest score she can get is
Mean = ( Σx) / n
80=(85+83+86+f)/4
80×4= 254+f
Therefore, f= 320-254=66
Therefore the minimum score she can have to have a B is 66.
Then, let take the upper limit mean 89. i.e the maximum she can have so that she don't have an A grade.
Mean = ( Σx) / n
89=( 83+85+86+f)/4
89×4= 254+f
f= 356-254
f=102.
Therefore this shows that she cannot have an A grade in the exam. The maximum score for the exam is 100.
There the range of score is 66 ≤ f ≤100 to have a B grade
66 ≤ f ≤100 answer
Since she cannot score 102 in the examination.
Answer:
9*(6+7)
Step-by-step explanation:
First, we have to find the Greatest Common Factor (GCF), to do this we have to see all the factors of 54 and 63 and find the greatest factor that they have in common.
Factors of 54
1,2,3,6,9,18,27,54
Factors of 63
1,3,7,9,21,63
The GCF is 9 because is the greatest factor that is common to both numbers.
Now we have to divide 54/9 and 63/9
54/9 = 6
63/9 = 7
So now we can write the product of the GCF and another sum:
9*(6+7)
<em>We can prove this by solving both expressions:</em>
<em>54+63 = 9*(6+7)</em>
<em>117 = 9*13</em>
<em>117 = 117 </em>
<em>The results are equal so we prove it is right.</em>